The occurrence of multiple treatment switches in axial spondyloarthritis. Results from five Nordic rheumatology registries. (23rd December 2021) - Di Giuseppe, Daniela; Lindström, Ulf; Aaltonen, Kalle; Relas, Heikki; Provan, Sella; Gudbjornsson, Bjorn; Hetland, Merete Lund; Askling, Johan; Kauppi, Markku; Geirsson, Arni Jon; Chatzidionysiou, Katerina; Jørgensen, Tanja Schjødt; et al.
Abstract: Objectives: In axial spondyloarthritis (axSpA), switching between multiple biologic or targeted synthetic (b/ts-) DMARDs might indicate difficult-to-treat disease. We aimed to explore the occurrence of multiple switching in routine care axSpA patients using various definitions, and to identify associated clinical characteristics upon start of first b/tsDMARD (baseline). Methods: Observational cohort study including patients with axSpA starting a first-ever b/tsDMARD 2009–2018 based on data from five biologic registries (Denmark/Sweden/Finland/Norway/Iceland). Comorbidities and extra-articular manifestations were identified through linkage to national registries. Multi-switching was defined in overlapping categories according to b/tsDMARD treatment history: treatment with ≥3, ≥4 or ≥5 b/tsDMARDs during follow-up. We explored the cumulative incidence of patients becoming multi-switchers with ≥3 b/tsDMARDs stratified by calendar-period (2009–2011, 2012–2013, 2014–2015, 2016–2018). In the subgroup of patients starting a first b/tsDMARD 2009–2015, baseline characteristics associated with multi-switching (within 3 years' follow-up) were explored using multiple logistic regression analyses. Results: Among 8398 patients included, 6056 patients (63% male, median age 42 years) started a first b/tsDMARD in 2009–2015, whereof proportions treated with ≥3, ≥4 or ≥5 b/tsDMARDs within 3 years' follow-up were 8%, 3% and 1%, respectively. Calendar-period did not affect the cumulative incidence of multi-switching. Baseline characteristics associated with multi-switching (≥3 b/tsDMARDs) were female gender, shorter disease duration, higher patient global score, comorbidities and having psoriasis but not uveitis. Conclusion: In this large Nordic observational cohort of axSpA patients, multiple switching was frequent with no apparent time-trend. Clinical associated factors included gender, but also previous comorbidities and extra-articular manifestations illustrating the ongoing challenge of treating this patient group.